Does intraoperative reduction result in better outcomes in low-grade lumbar spondylolisthesis after transforaminal lumbar interbody fusion? A systematic review and meta-analysis - Qin, Rongqing; Zhu, Min; Zhou, Pin; Guan, Anhong (Frontiers in Medicine, 2024)
Objective This study aimed to compare the clinical efficacy and safety of reduction vs. arthrodesis in situ with transforaminal lumbar interbody fusion (TLIF) for low-grade lumbar spondylolisthesis. Study design Systematic review and meta-analysis. Methods A comprehensive literature search was implemented in PubMed, Embase, and Cochrane Library databases. Randomized or non-randomized controlled trials that were published until July 2023 that compared reduction vs. arthrodesis in situ techniques with minimally invasive or open-TLIF for low-grade spondylolisthesis were selected. The quality of the included studies was evaluated by the Newcastle–Ottawa Scale (NOS). Data were extracted according to the predefined outcome measures, including operation time and intraoperative blood loss; short- and long-time follow-up of visual analog scale (VAS) back pain (VAS-BP) and Oswestry Disability Index (ODI); slippage and segmental lordosis; and the complication and fusion rate. Results Five studies (n = 495 patients) were finally included. All of them were retrospective cohort studies with Evidence Level II. The pooled data revealed that both techniques had similar patient-reported outcomes (VAS, ODI, and good and excellent rate) during short- and long-term follow-up. In addition, no significant differences were observed in the fusion and complication rates. However, although the reduction group did achieve better slippage correction, it was associated with increased operation time and intraoperative blood loss compared with the in situ arthrodesis group. Conclusions Based on the available evidence, intraoperative reduction does not result in better clinical outcomes in low-grade spondylolisthesis after minimally invasive or open-TLIF, and the in situ arthrodesis technique could be an alternative.